Owls lack UV-sensitive cone opsin and red oil droplets, but see UV light at night: Retinal transcriptomes and ocular media transmittance. (May 2019) - Höglund, Julia; Mitkus, Mindaugas; Olsson, Peter; Lind, Olle; Drews, Anna; Bloch, Natasha I.; Kelber, Almut; Strandh, Maria
Graphical abstract: Highlights: The lack of a functional SWS1 gene in owls is confirmed. Owls also lack the enzyme required for red pigmentation L cone oil droplets. The ocular media of owls transmit large amounts of ultraviolet. Owls likely have trichromatic colour vision in daylight. UV-transmittance of the ocular media make rod vision of owls more sensitive. Abstract: Most diurnal birds have cone-dominated retinae and tetrachromatic colour vision based on ultra-violet/violet-sensitive UV/V cones expressing short wavelength-sensitive opsin 1 (SWS1), S cones expressing short wavelength-sensitive opsin 2 (SWS2), M cones expressing medium wavelength-sensitive opsin (RH2) and L cones expressing long wavelength-sensitive opsin (LWS). Double cones (D) express LWS but do not contribute to colour vision. Each cone is equipped with an oil droplet, transparent in UV/V cones, but pigmented by carotenoids: galloxanthin in S, zeaxanthin in M, astaxanthin in L and a mixture in D cones. Owls (Strigiformes) are crepuscular or nocturnal birds with rod-dominated retinae and optical adaptations for high sensitivity. For eight species, the absence of functional SWS1 opsin has recently been documented, functional RH2 opsin was absent in three of these. Here we confirm the absence of SWS1 transcripts for the Long-eared owl ( Asio otus ) and demonstrate its absence for the Short-eared owl ( Asio flammeus ), Tawny owl ( Strix aluco ) and Boreal owl ( Aegolius funereus ). All four species had transcripts of RH2, albeit with low expression. All four species express all enzymes needed to produce galloxanthin, but lack CYP2J19 expression required to produce astaxanthin from dietary precursors. We also present ocular media transmittance of the Eurasian eagle owl ( Bubo bubo ) and Short-eared owl and predict spectral sensitivities of all photoreceptors of the Tawny owl. We conclude that owls, despite lacking UV/V cones, can detect UV light. This increases the sensitivity of their rod vision allowing them, for instance, to see UV-reflecting feathers as brighter signals at night.